2005
DOI: 10.3758/bf03195325
|View full text |Cite
|
Sign up to set email alerts
|

Directed forgetting of autobiographical events

Abstract: Two diary experiments demonstrated directed forgetting (DF) of autobiographical events, previously observed only for less complex memory items. Using a 2-week diary paradigm, we compared recall between a group of participants who were directed to forget Week 1 memories (forget group) and a group who did not receive a forget instruction (remember group). In Experiment 1, the forget group remembered fewer items from Week 1 than did the remember group. The effect was observed for negative and positive valence eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 42 publications
3
35
0
Order By: Relevance
“…The motivation category indicates that people sometimes claim to have succeeded in reducing or eliminating belief in events, even while the recollective image remains vivid. Although this category is partly reminiscent of work on intentional/directed forgetting of events (Anderson & Greene, 2001), and there is some evidence that memory for autobiographical events can be intentionally suppressed (Joslyn & Oakes, 2005;Noreen & Macleod, 2013), these studies focus on the intentional forgetting of recollective information, whereas our participants reported suppressing belief in the event but not recollective information. Theories of intentional forgetting will need to account for how belief in the occurrence of events is eliminated, both when recollection is and is not also reduced.…”
Section: Personal Motivation To Alter Autobiographical Beliefmentioning
confidence: 81%
“…The motivation category indicates that people sometimes claim to have succeeded in reducing or eliminating belief in events, even while the recollective image remains vivid. Although this category is partly reminiscent of work on intentional/directed forgetting of events (Anderson & Greene, 2001), and there is some evidence that memory for autobiographical events can be intentionally suppressed (Joslyn & Oakes, 2005;Noreen & Macleod, 2013), these studies focus on the intentional forgetting of recollective information, whereas our participants reported suppressing belief in the event but not recollective information. Theories of intentional forgetting will need to account for how belief in the occurrence of events is eliminated, both when recollection is and is not also reduced.…”
Section: Personal Motivation To Alter Autobiographical Beliefmentioning
confidence: 81%
“…Thus, people can still intentionally forget the memory which was enhanced by the self-referential processing. Some other studies investigated the directed forgetting of recently autobiographical memories [39], [40]. The results suggested that both the negative and the positive autobiographical memories can be directed forgotten.…”
Section: Introductionmentioning
confidence: 99%
“…With some exceptions (e.g., Barnier et al, 2007;Burwitz, 1974;Golding & Keenan, 1985;Gottlob, Golding, & Hauselt, 2006;Joslyn & Oakes, 2005), the majority of directed forgetting research has been dominated by the memorization of word lists. However, many everyday memories are about actions that were performed or about activities that we participated in.…”
mentioning
confidence: 99%